Impact of Inter-eNodeB Handover Pameters on Performance Optimization of LTE Networks - Mina Malekzadeh; Fatemeh Rezaiee (Institute of Advanced Engineering and Science, 2018)
Handover, as a resource consuming process, is an important issue in mobile communications which can highly affect the overall performance of the LTE networks. Since the handover process mainly relies on four main entry condition parameters, optimizing these parameters will in turn improve the handover process. In this work, we investigate the effectiveness of the four handover parameters by measuring the resulting downlink throughput and number of the required handovers. We furthermore determine the optimized values of the parameters through implementing different sets of experiments. Finally, by applying the obtained optimized parameters on two main LTE handover algorithms i.e. A3RSRP and A2A4RSRQ, their performance is compared regarding to different speeds of the mobile equipment. We determine how to accurately select the optimal settings for the parameters so that greater LTE performance can be achieved.